2011
DOI: 10.1093/ageing/afr005
|View full text |Cite
|
Sign up to set email alerts
|

Is power training or conventional resistance training better for function in elderly persons? A meta-analysis

Abstract: Objective: to determine the effects of power training with high movement velocity compared with conventional resistance training with low movement velocity for older community-dwelling people. Design: systematic review of randomised controlled trials. Data sources: the Cochrane Central Register of Controlled Trials, PubMed (Medline), EMBASE, CINAHL, PEDro and Scholar-Google. Trials: all randomised or quasi-randomised trials investigating power training with high movement velocity versus conventional resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
94
1
26

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(129 citation statements)
references
References 30 publications
6
94
1
26
Order By: Relevance
“…Although arterial hypertension was the most frequent health condition, no cardiovascular problems were reported during the intervention period. The average perceived exertion was 12.8±1.1 (11)(12)(13)(14), which corresponds to 'somewhat hard' on the Borg Scale.…”
Section: Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…Although arterial hypertension was the most frequent health condition, no cardiovascular problems were reported during the intervention period. The average perceived exertion was 12.8±1.1 (11)(12)(13)(14), which corresponds to 'somewhat hard' on the Borg Scale.…”
Section: Safetymentioning
confidence: 99%
“…In these subjects, loads equal to 40% of one maximal resistance (1MR) were able to increase muscle power because of the gains in movement speed 8,9 . Power training has been shown to be safe and well tolerated in older adults 10 , however there is a need to determine possible adverse events associated with the training of fast movements in frail, sedentary older adults with functional deficits 10,11 . There is still no evidence that this kind of exercise can be safe and tolerated by subjects with PD, although safety is the main concern for these subjects when deciding to participate in a clinical trial 12 .…”
Section: Introductionmentioning
confidence: 99%
“…También los autores dan la opción de un entrenamiento de alta intensidad en adultos mayores con suficiente aptitud y experiencia y que trabajen en entornos supervisados. Sobre la potencia, Tschopp et al (2011), en un meta-análisis, observaron que la mayoría de los estudios utilizaron sesiones de entrenamiento con 2-3 series de 8-12 repeticiones tres veces por semana durante un período de 8-16 semanas, con un máximo de 24 semanas, todo lo anterior a una alta velocidad y baja carga que estaba entre 40%-75% de 1RM.…”
Section: Características Del Entrenamiento De Fuerza En Personas Mayoresunclassified
“…Respecto al entrenamiento de la potencia, Tschopp, et al (2011) hicieron un meta-análisis comparando los efectos de entrenamientos de fuerza a baja velocidad versus los que incluían velocidades más altas y donde participaron personas mayores. Incluyeron ensayos aleatorios o ensayos con asignaciones diferentes clasificando 11 estudios que vincularon a 377 casos.…”
Section: Sección Centralunclassified
“…Nevertheless, there is not a consensus on the best method to achieve this goal, although strength training and, particularly, power training have been shown to be suitable. 8 Indeed, Tschopp et al 8 found both strength and power training to be an effective strategy to reverse senescent functional decline. The authors, however, elect power training as the best method because similar results can be achieved with 20% less training volume.…”
Section: Introductionmentioning
confidence: 99%